Tree rings reveal globally coherent signature of cosmogenic radiocarbon events in 774 and 993 CE - Ulf Büntgen (Nature Communications, 2018)
Despite their extensive use, the absolute dating of tree-ring chronologies has not hitherto been independently validated at the global scale. Here, the identification of distinct 14C excursions in 484 individual tree rings, enable the authors to confirm the dating of 44 dendrochronologies from five continents.